Implementasi Pembelajaran PAI Untuk Mewujudkan Moderasi Beragama Di SMA PGRI Kedamean - Fitri Indah Sari Fitri; Sutono; Suparno (Jurnal Pendidikan Agama Islam Miazhar, 2022)
SMA PGRI Kedamean is a public school which indicates that the school is plural and consists of various religions of its students. Living in the midst of differences will be difficult for students who are unable to accept and appreciate these differences. Each individual has different characteristics, backgrounds, religions, ethnicities, and languages. If these differences are not resolved wisely, it can lead to conflicts and divisions in the class. The realization of religious moderation in the learning process can certainly be achieved by incorporating the basic principles or values of religious moderation into the learning process. Research on the Implementation of PAI Learning to Realize Religious Moderation at SMA PGRI Kedamean. This study aims to describe: (1) Planning for PAI learning to achieve religious moderation, (2) Implementation of PAI learning to achieve religious moderation, (3) Evaluation of PAI learning to achieve religious moderation. This type of research is descriptive qualitative which discusses the form of implementation of PAI learning to realize religious moderation in Kedamean PGRI High School. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, data validity, and conclusion drawing. The results of this study indicate that: PAI learning planning to realize religious moderation at SMA PGRI Kedamean has been maximized in terms of the preparation of the syllabus and the development of the lesson plans, wherein the syllabus itself has been inserted (inserted) about religious moderation while in the lesson plan used the value of religious moderation is realized both with learning methods or models as well as with material adjustments that contain religious moderation values. The implementation of PAI learning to realize religious moderation is carried out by using appropriate learning methods such as the use of the lecture method, and discussions both direct discussions and group discussions. , respecting others, establishing intimacy, having social concern, having a nationalist spirit, being tolerant, and obeying the rules